Hubungan Antarpribadi dalam Film Pendek “Tak Lagi Sama”: Perspektif Sosiologi Komunikasi - Nanda Syukerti; Lovia Evanne; Ani Sagita (Universitas Muhammadiyah Kotabumi, 2021)
In forming individuals, interpersonal relationships have an important role, through interpersonal relationships are expected to be able to encourage someone to have feelings, understanding, and support and help individuals to understand the expectations of other individuals. There are several theories to reduce this phenomenon, which specifically generalizes the concept of interpersonal relationships which have an important role in shaping individuals, through interpersonal relationships are expected to be able to encourage someone to have a feeling, understanding and support and help individuals to understand the expectations of others. Another individual In the film